An Unusual Carbohydrate Conformation is Evident in Moraxella catarrhalis Oligosaccharides - Martin Frank; Patrick M. Collins; Ian R. Peak; I. Darren Grice; Jennifer C. Wilson (Molecules, 2015)
Oligosaccharide structures derived from the lipooligosaccharide of M. catarrhalis show that the highly branched glucose-rich inner core of the oligosaccharide has an altered conformation compared to the most truncated tetra-glucose-Kdo lgt1/4Δ oligosaccharide structure. Addition of one residue each to the (1-4) and (1-6) chains to give the lgt2Δ oligosaccharide is the minimum requirement for this conformational change to occur. Extensive molecular modeling and NMR investigations have shown that the (1-3), (1-4), and (1-6) glycosidic linkages from the central α-D-Glcp have significantly altered conformational preferences between the two structures. For the lgt1/4Δ oligosaccharide the (1-3) and (1-4) linkage populates predominantly the syn minimum on the conformational free energy map and for the (1-6) linkage conformational flexibility is observed, which is supported by 1H-NMR T1 measurements. For the lgt2Δ oligosaccharide the unusual “(1-4)anti-ψ(1-6)gg” conformation, which could be confirmed by long-range NOE signals, is a dominant conformation in which the oligosaccharide is very compact with the terminal α-D-GlcNAc residue folding back towards the center of the molecule leading to an extensive intra-molecular hydrophobic interaction between the terminal residues. Comparing effective H-H distances, which were calculated for conformational sub-ensembles, with the NOE distances revealed that typically multiple conformations could be present without significantly violating the measured NOE restraints. For lgt2Δ the presence of more than one conformation is supported by the NOE data.